DAMPAK EKSPLORASI MIGAS PETROCHINA TERHADAP KETAHANAN ENERGI IDONESIA - Puji Chaerani (WANUA : Jurnal Hubungan Internasional, 2020)
This research portrays the bilateral relations of Indonesia and People’s Republic of China on oil and gas sector through PetroChina’s exploration as a tool for gaining the nations energy interest. The aims of this research is to discover its strategy and the impact towards the Indonesia’s energy sustainability. This study focuses on PetroChina’s strategy and its impact in the priod of 2002-2012. The type of research is Descriptive-Analytic research. Data collecting technique used are library research, as well as gathering information from various written sources such as books, journals, documents, and scientific articles. The result of this study shows that strategy of PetroChina’s in oil and gas sector in Indonesia are to establish new companies, build partnerships to increase the popularity of the company, and accommodate the local society. It become threaten by affordable, accesable, and reliable of Indonesia’s oil and gas. It happen because this exploration is more dominant to the oil and gas interest of the People’s Republic of China. Penelitian ini menggambarkan hubungan bilateral Indonesia dengan RRT dalam bidang migas melalui eksplorasi oleh PetroChina sebagai alat dalam mencapai kepentingan energi kedua negara. Penelitian ini bertujuan untuk mengetahui strategi dan dampaknya terhadap ketahanan energi Indonesia. Pembahasan difokuskan pada strategi PetroChina dan dampak eksplorasinya terhadap ketahanan energi dalam kurun waktu 2002-2012. Tipe penelitian adalah Deskriptif-Analitik. Teknik pengumpulan data, diperoleh dari studi pustaka yang menelaah sejumlah buku, jurnal, dokumen, dan artikel ilmiah. Hasil penelitian menunjukkan bahwa strategi PetroChina dalam bidang migas yaitu membentuk anak perusahaan baru, membangun kemitraan untuk meningkatkan popularitas perusahaan, dan mengakomodasi masyarakat lokal. PetroChina menjadikan ketahanan energi menjadi terancam terhadap affordable, accesable, dan reliable migas Indonesia karena hasil eksplorasi PetroChina lebih dominan ditujukan untuk kepentingan migas nasional RRT.